Management of spontaneous pneumothorax and post-interventional pneumothorax: German S3 guideline - Schnell, Jost; Beer, Meinrad; Eggeling, Stephan; Gesierich, Wolfgang; Gottlieb, Jens Tobias; Herth, Felix; Hofmann, Hans-Stefan; Jany, Berthold; Kreuter, Michael; Ley-Zaporozhan, Julia; Scheubel, Robert; Walles, Thorsten; et al. (Respiration, 2019)
In Germany, 10,000 cases of spontaneous pneumothorax are treated inpatient every year. The German Society for Thoracic Surgery, in co-operation with the German Society for Pulmonology, the German Radiological Society, and the German Society of Internal Medicine has developed an S3 guideline on spontaneous pneumothorax and post-interventional pneumothorax moderated by the German Association of Scientific Medical Societies. Method: Based on the source guideline of the British Thoracic Society (2010) for spontaneous pneumothorax, a literature search on spontaneous pneumothorax was carried out from 2008 onwards, for post-interventional pneumothorax from 1960 onwards. Evidence levels according to the Oxford Center for Evidence-Based Medicine (2011) were assigned to the relevant studies found. Recommendations according to grade (A: “we recommend”/“we do not recommend,” B: “we suggest”/“we do not suggest”) were determined in 3 consensus conferences by the nominal group process. Results: The algorithms for primary and secondary pneumothorax differ in the indication for CT scan as well as in the indication for chest drainage application and video-assisted thoracic surgery. Indication for surgery is recommended individually taking into account the risk of recurrence, life circumstances, patient preferences, and procedure risks. For some forms of secondary pneumothorax, a reserved indication for surgery is recommended. Therapy of post-interventional spontaneous pneumothorax is similar to that of primary spontaneous pneumothorax. Discussion: The recommendations of the S3 Guideline provide assistance in managing spontaneous pneumothorax and post-interventional pneumothorax. Whether this will affect existing deviant diagnostic and therapeutic measures will be demonstrated by future epidemiological studies.
Gesehen am 25.07.2019